Gilroy Garlic Festival discounts tickets for chef team supporters - Uribes, Tom::::::::: (2013)
Discount tickets for the 35th Gilroy Garlic Festival, where Fresno State chefs will compete in the inaugural Garlic Bowl 2-4 p.m. Friday, July 26, are available to Red Wavers who want to support the team.